Munkaerő-piaci folyamatok a szlovák-magyar határ mentén - Szabó, Ingrid (Közép-Európai Közlemények, 2010)
The author of the study aims to provide a brief overview of the peculiarities of labor markets situated along borders. The paper highlights the differences between the two sides of the border: counties and micro-regions on the Hungarian side are more developed than the average, while counties on the Slovakian side belong to the backward regions of the country, and are hit by severe unem-ployment. The paper presents statistical data to illustrate the changes in the unemployment rate in Southern-Slovakia and the decrease in it, which could be experienced in the mid-2000s due to job new opportunities across the border. It provides detailed information on the impacts of the Industrial Park in Komárom on the region’s labor market. The economic recession halted and reversed the previous, favorable tendencies: North-Hungarian and local companies cannot provide work any longer, so the region’s unemployment rate rocketed again.